Empowerment technologies - Sagun, Marc Lhester John A. (Makati City : Diwa Learning Systems, Inc., 2019)
"Being technical-savvy seems to be an innate characteristic among today's younger generation. This is done to promote the responsible use of technology and to become aware that technology can be a tool to promote social change. Technology is powerful only if you can use it well to your advantage. This book is an important tool toward further developing your basic knowledge and skills in line with technology so that you are prepared to use it for your eventual professional endeavors. The knowledge and skills that you will gain from this resource will open greater opportunities for your productivity, learning, and fulfillment of your social responsibility".
Includes bibliography.
English text.
Keywords: Information technology; Computer networks